PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PELANGGAN MENGGUNAKAN JASA TERATAI LAUNDRY MEDAN - Samuel Tenang Ukur Ardianta Ginting; Aldi Ginting (JURNAL REGIONOMIC, 2021)
The laundry business, namely Teratai Laundry Medan, runs its business using a service marketing mixor commonly called 7P. Therefore, this study aims to determine the effect of the marketing mix oncustomer decisions to use the services of Teratai Laundry Medan. This study uses a descriptive methodwith data collection techniques, namely observation, interviews, questionnaires, and documentarystudies. The population is all consumers of Teratai Laundry Medan. The sample of this study was 100people with a sampling technique in the form of purposive sampling, considering that consumers makepayments on their own behalf and have used laundry services at least 2 times. The data analysis of thisresearch is in the form of multiple linear regression quantitative analysis, used to determine the effectof the marketing mix consisting of 7 independent variables, namely product (X1), price (X2), place (X3),promotion (X4), people (X5), process ( X6), physical evidence (X7) against customer decisions. Theanalysis uses SPSS software version 24.0 to make it easier to process and interpret research results.Most of the respondents in this study were male, aged 20-29 years, high school education level, workedas a private employee, and had an income of Rp. 1,500,000 – Rp. 2,499,000. Determination (R2) showsa value of 0.50. The correlation coefficient (R) shows a value of 0.71. The partial F analysis test showsthat the calculated F is greater than the F table (13,35 > 2,10) which means Ho is rejected and Ha is accepted. The t-test results show thatproduct and place have a partial effect, then price, promotion, people, process, and physical evidencehave no partial effect on purchasing decisions.